Data Sovereignty in Inter-organizational Information Systems - Opriel, Sebastian; Möller, Frederik; Strobel, Gero; Otto, Boris (Business & Information Systems Engineering, 2024)
Car manufacturers and suppliers in the Automotive industry increasingly face the issue of optimization of highly complex supply chains that need to accommodate each customer's precise demands, requiring a vast array of parts and information to be available at the right place and at the right time. This involves data sharing between organizations, which is hindered by various issues, such as fear of data misappropriation by the data receiver or the involuntary disclosure of business secrets. The paper proposes design principles for a novel type of Inter-Organizational Information System, which addresses these challenges through the technical implementation of data sovereignty. The study reports on an Action Design Research study in the Automotive industry between a car manufacturer and a 1st-tier supplier. It contributes (a) design requirements, (b) design features, (c) an instantiation, and (d) design principles for this type of data sovereign inter-organizational information system.
Keywords: Data sovereignty; Inter-organizational information systems; Usage control; Action design research; Design principles